Macro and Micro-anatomy of Tokay Gecko’s Reproduction Organs and Growth of External Body in Support on Reproduction Activities (Squamata: Gekkonidae: Gekko gecko) - Kurniati, Hellen; Phadmacanty, Ni Luh Putu Rischa (Jurnal Veteriner, 2021)
Tokay gecko, Gekko gecko is an oviparous lizard that is distributed very widely in tropical Asia. The sexual maturity stage of tokay gecko does not have seasonal reproductive activity; they reproduce along the year. The study on the reproduction organ and growth of external morphology of tokay gecko is the first contribution to further scientific information.  Gonadal micro-anatomy that were shown by histology and macro-anatomy to include the sex accessories could be demonstrated in this lizard as a criteria for the reproductive activity of urogenital organs.  Males and females tokay gecko have simple urogenital track systems and also the males have simple hemipenis morphology.  Testes position inside the male body is not symmetric, in the right testis is always in a higher position than left testis.  Based on analysis of the measurement of the posterior part of the body, the width of cloaca, width of base tail and length of hind limb increase asymptotic growth on snout to vent length (SVL) SVL?130 mm for females, and SVL?150 mm for males.  Asymptotic growth in the posterior part of the male and female body is a form of co-evolution, besides the male urogenital organs and the female reproductive system which also support co-evolution in the reproductive organs.